Efficient Control of a Mesoporous Fibrillar PEDOT:PSS Aerogel Structure for Promising Thermoelectric Applications - Weinbach, Quentin; Thakkar, Swapneel Vijay; Carvalho, Alain; Chaplais, Gérald; Combet, Jérôme; Constantin, Doru; Stein, Nicolas; Collin, Dominique; Biniek, Laure (Frontiers in Electronic Materials, 2022)
In this study, we describe a reproducible process route to form highly mesoporous, mechanically robust and handleable aerogels based on entangled PEDOT:PSS nanofibers. The conservation of the alcogel 3D network is ensured via thorough control of the solvent exchange and drying steps. Particular consideration has been given to metrology, allowing us to fully characterize the thermoelectric properties of the aerogels. The interconnected fibrillar morphology provides good electrical conductivity and mechanical properties by forming effective pathways for both electron transfer and sustaining mechanical forces. The Seebeck coefficient does not seem to be impacted by the high porosity of the material. Finally, the positive impact of mesoporosity on thermal transport and in particular on the lattice part of the thermal conductivity (klat) is demonstrated here for the first time. Thus, this pure PEDOT:PSS aerogel exhibits very interesting structural and charge transport properties. The high power output of 2µW, measured for a temperature gradient of 36.5 K on a single aerogel sample, highlights the possibility of integrating PEDOT:PSS aerogels into thermoelectric generators.